Comportamiento de los depósitos y colocaciones en las cajas municipales de ahorro y crédito en las regiones de Loreto y Ucayali periodo 2015 - 2019 - Marreros Zamudis, Maria Alvina (2021)
Banks in the Loreto and Ucayali region, period 2015 - 2019, the research is applied with a quantitative approach at a descriptive level and a non-experimental design. The results show that the Loreto region is the one with the highest amount of deposits and placements, with the balance of deposits as of 2019 being 249 million new suns and in placements 330 million new suns; In the Ucayali region, fund-raising at the end of 2019 reached only the amount of 87 million and the placements the amount of 302 million new suns; in this region (Ucayali) deposits only represent 28.9% of placements, while in the Loreto region they represent 75%